Self-induced transparency in InGaAs quantum-dot waveguides - Schneider, S.; Borri, P.; Langbein, W.; Woggon, U.; Förstner, Jens; Knorr, A.; Sellin, R. L.; Ouyang, D.; Bimberg, D. (Applied Physics Letters)
We report the experimental observation and the theoretical modeling of self-induced-transparency signatures such as nonlinear transmission, pulse retardation and reshaping, for subpicosecond pulse propagation in a 2-mm-long InGaAs quantum-dot ridge waveguide in resonance with the excitonic ground-state transition at 10 K. The measurements were obtained by using a cross-correlation frequency-resolved optical gating technique which allows us to retrieve the field amplitude of the propagating pulses.
Keywords: tet_topic_qd

Online-Marktforschung - Analyse von Konsumentenverhalten in virtuellen Umgebungen, in: Information Management & Consulting, 18,2 - Schryen, Guido; Herstell, Jan (IM : die Zeitschrift für Information Management und Consulting)

Internet-Wahlen - Schryen, Guido (6. Internationale Tagung Wirtschaftsinformatik)
Zusammenfassung: Im Rahmen des E-Governments werden zunehmend Internetwahlen diskutiert. Der Beitrag diskutiert zunächst die Vor- und Nachteile derartiger Wahlen und zeigt Anwendungsgebiete sowie durchgeführte Pilotprojekte im politischen wie auch wirtschaftlichen Bereich auf. Im Rahmen eines Anforderungssystems werden anschließend aus demokratischen Wahlgrundsätzen sicherheitstechnologische Anforderungen herausgearbeitet. Zu deren Adressierung werden kryptographischen Wahlkonzepte herangezogen, von denen die wichtigsten vorgestellt werden. Aufgrund der Komplexität der Anforderungslandschaft wird ein sicherheitstechnologisches Strukturmodell vorgestellt, das insbesondere dazu dient, die Sicherheit(skomponenten) eines Wahlsystems systematisch mit den Anforderungen abzugleichen. Der Artikel schließt mit einem Ausblick auf notwendige Untersuchungen.
Keywords: Internet-Wahlen; E-Democracy; Sicherheit; Kryptographie

Phonon-Assisted Damping of Rabi Oscillations in Semiconductor Quantum Dots - Förstner, Jens; Weber, C.; Danckwerts, J.; Knorr, A. (Physical Review Letters)
Keywords: tet_topic_qd

Auf ein Wort - Moeglichkeiten und Grenzen der automatischen Spracherkennung - Haeb-Umbach, Reinhold (Forschungsforum Paderborn)

[Rez. v.] Frauke Reitemeier: Deutsch-englische Literaturbeziehungen. Der historische Roman Sir Walter Scotts und seine deutschen Vorläufer (=Beiträge zur englischen und amerikanischen Literatur. 18). Paderborn u.a. Ferdinand Schöningh 2001 - Süßmann, Johannes (IASL online)
Keywords: Geschichtsroman; Scott; Walter; Naubert; Benedikte

[Rez. v.] Stefan Ehrenpreis / Ute Lotz-Heumann: Reformation und konfessionelles Zeitalter (=Kontroversen um die Geschichte), Darmstadt 2002 - Süßmann, Johannes (sehepunkte)
Keywords: Gedenken; Reformation

Direct parameter specification of an attention shift: Evidence from perceptual latency priming. - Scharlau, Ingrid; Ansorge, Ulrich (Vision Research)
In the direct parameter specification (DPS) mode of sensorimotor control, response parameters can be specified by stimuli that are not consciously perceived [Psychological Research/Psychologische Forschung 52 (1990) 207]. DPS is contingent on the current intentions. The invisible stimuli can be processed for the purposes of sensorimotor control only if they match the actual intentions, for example, share task-relevant features. The present experiments explore whether attentional capture by masked abrupt-onset stimuli is mediated via DPS. Participants judged which of two visual targets appeared first. Masked primes preceded one of the targets. The primes were either similar to the targets or not, in shape, or in color. Target-like (task-relevant), but not distractor-like (task-irrelevant), primes facilitated perceptual latencies of targets trailing at their positions. Thus, the latency effects resulted from DPS of an attention shift, rather than from bottom-up capture or from top-down
Keywords: direct parameter specification; DPS; attention shift; latency priming; sensorimotor control; stimuli; task-relevant features; visual targets; color; shape; latency effects; Adult; Attention; Discrimination (Psychology); Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Visual Perception; Attention; Perceptual Motor Processes; Response Latency; Stimulus Onset; Visual Stimulation; Form and Shape Perception; Sensory Adaptation

Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional interpretation. - Scharlau, Ingrid; Neumann, Odmar (Psychological Research)
Four experiments investigated the influence of a metacontrast-masked prime on temporal order judgments. The main results were (1) that a masked prime reduced the latency of the mask's conscious perception (perceptual latency priming), (2) that this effect was independent of whether the prime suffered strong or weak masking, (3) that it was unaffected by the degree of visual similarity between the prime and the mask, and that (4) there was no difference between congruent and incongruent primes. Finding (1) suggests that location cueing affects not only response times but also the latency of conscious perception. (2) The finding that priming was unaffected by the prime's detectability argues against a response bias interpretation of this effect. (3) Since visual similarity had no effect on the prime's efficiency, it is unlikely that sensory priming was involved. (4) The lack of a divergence between the effects of congruent and incongruent primes implies a functional difference between t
Keywords: perceptual latency priming; temporal order judgments; masked stimuli; unmasked stimuli; attentional interpretation; response times; location cueing; visual perception; Adult; Attention; Female; Humans; Male; Models; Psychological; Perceptual Masking; Psychometrics; Reaction Time; Task Performance and Analysis; Time Perception; Masking; Reaction Time; Response Latency; Stimulus Parameters; Visual Contrast; Attention; Cues; Priming; Temporal Frequency; Temporal Order (Judgment)

Temporal parameters and time course of perceptual latency priming. - Scharlau, Ingrid; Neumann, Odmar (Acta Psychologica)
Visual stimuli (primes) reduce the perceptual latency of a target appearing at the same location (perceptual latency priming, PLP). Three experiments assessed the time course of PLP by masked and, in Experiment 3, unmasked primes. Experiments 1 (N=11; mean age 26.9) and 2 (N=12; mean age 25.6) investigated the temporal parameters that determine the size of priming. Stimulus onset asynchrony was found to exert the main influence accompanied by a small effect of prime duration. Experiment 3 (N=19; mean age 27.7) used a large range of priming onset asynchronies. We suggest to explain PLP by the Asynchronous Updating Model which relates it to the asynchrony of 2 central coding processes, preattentive coding of basic visual features and attentional orienting as a prerequisite for perceptual judgments and conscious perception. (PsycINFO Database Record (c) 2017 APA, all rights reserved)
Keywords: perceptual latency priming; temporal parameters; Asynchronous Updating Model; time course; stimulus onset asynchrony; visual masking; attention; Adult; Attention; Female; Humans; Male; Perceptual Masking; Reaction Time; Time Perception; Visual Perception; Attention; Priming; Stimulus Onset; Visual Masking; Visual Perception; Models; Time

Personale Bedingungen reziproker Eltern-Kind-Beziehungen - Buhl, Heike M. (Jugendzeit - Time out? Die Ausgestaltung des Jugendalters als Moratorium)

Hybride Technologien: Technowissenschaftsforschung als transdisziplinäre Erkenntnispolitik - Weber, Jutta (Achsen der Differenz. Gesellschaftstheorie & feministische Kritik II)

Technowissenschaftskultur und feministische Kritik. Eine programmatische Einleitung - Weber, Jutta; Bath, Corinna (Turbulente Körper und soziale Maschinen. Feministische Studien zur Technowissenschaftskultur)

Umkämpfte Bedeutungen: Naturkonzepte im Zeitalter der Technoscience. : Campus 2003 - Weber, Jutta

Turbulente Körper und soziale Maschinen. Feministische Studien zur Technowissenschaftskultur

Globalization and Self-Organization in the Knowledge-Based Society - Fuchs, Christian (tripleC)

Co-operation and self-organisation - Fuchs, Christian (tripleC (Cognition, Communication, Co-operation))

The Role of the Individual in the Social information process - Fuchs, Christian (Entropy)

The Self-Organization of Matter - Fuchs, Christian (Nature, Society, and Thought)

Echos in Festkörpern - Meier, Torsten; Thomas, P. (Physik Journal)

Many-body Coulomb effects in the optical properties of semiconductor heterostructures - Meier, Torsten; Pasenow, B.; Thomas, P.; Koch, S.W. (Germany NIC Series, Vol. 20)

Markovprozesse zur Modellierung bei Codekompression - Hoppe, Ulrich
Keywords: Diplomarbeit

Implementierung eines arithmetischen Dekodierers in Java - Unterkirchner, Claudia

Tabellenbasierte arithmetische Codierung - Kuntze, Daniel

Kontextuelle Kontingenz: Musikclips im wissenschaftlichen Umgang - Jacke, Christoph (Clipped Differences. Geschlechterrepräsentationen im Musikvideo)

Tabellenbasierte arithmetische Kodierung bei allgemeinen Alphabeten - Ackermann, Marcel R.
Keywords: Diplomarbeit

Mitarbeit im Sport : Bausteine zur Entwicklung einer Theorie des Sportvereins, dargelegt am Beispiel der Mitarbeitsverhältnisse und den strukturellen Bedingungen ihres Wandels - Meier, Heiko
Sportvereine unterliegen seit geraumer Zeit erheblichen Wandlungsprozessen. Neue und zunehmend auch größere Anforderungen und Erwartungen werden an die Vereine herangetragen, hervorgerufen durch Veränderungen im Steuerrecht, veränderte Sportverständnisse oder auch sich wandelnde Mitgliederinteressen. Hierauf reagieren die Vereine, indem sie neue Sportangebote schaffen oder neue Mitgliedschaftsbedingungen einführen sowie, nicht zuletzt, sowohl in den sportpraktischen als auch den administrativen Tätigkeitsbereichen zunehmend mehr bezahlte Mitarbeiter beschäftigen. Und die fortlaufenden Statistiken des Deutschen Sportbundes offenbaren den Erfolg dieser Maßnahmen: Waren zu Beginn der 1960er Jahre noch weniger als zehn Prozent der Gesamtbevölkerung im Vereinssport organisiert, liegt dieser Anteil mittlerweile bei knapp einem Drittel der Bevölkerung. In erster Linie zeichnen demnach die veränderten Strukturmerkmale der Sportvereine für das Wachstum des organisierten Sports verantwortlich. Angesichts der weiter steigenden Anforderungen an die Sportvereine ist zu vermuten, dass mehr und mehr Vereine solche Änderungen vornehmen werden. Der weitere Erfolg des organisierten Sports scheint also vorgezeichnet. Im Mittelpunkt dieser Veränderungen stehen dabei die Mitarbeitsverhältnisse in den Sportvereinen. Denn ehrenamtliche Mitarbeit ist für Sportvereine eine konstitutive Bedingung, weshalb die Ausweitung bezahlter Mitarbeitsverhältnisse nur komplementär hierzu verlaufen kann. Doch ist bislang noch nicht geklärt, welche langfristigen Folgen sich aus der zunehmenden Monetisierung der Sportvereinsarbeit ergeben werden und welche Grundbedingungen erfüllt sein müssen, um dieses komplementäre Verhältnis, insbesondere bei hauptberuflicher Mitarbeit, sicherstellen zu können. Dieser Problematik widmet sich die vorliegende Arbeit, indem die strukturellen Bedingungen der Mitarbeit in Sportvereinen nachgezeichnet und im Hinblick auf eine erfolgreiche Implementierung bezahlter Mitarbeitsverhältnisse analysiert werden. Dies setzt allerdings eine Betrachtung der grundlegenden Veränderungsmöglichkeiten der Sportvereine voraus. Denn nur so können Erklärungsansätze dafür geliefert werden, unter welchen Bedingungen ein Organisationswandel in den Vereinen stattfinden kann. Deshalb wird, unter besonderer Berücksichtigung der Chancen und Risiken einer Verberuflichung, eine systemtheoretisch angelegte Theorie des Vereins entwickelt, die zu einem tieferen Verständnis der Möglichkeiten zum Erhalt und Wandel von Sportvereinen führt.
Keywords: Sportverein; Mitarbeit; Organisationswandel; Professionalisierung; Verberuflichung; Sportvereinstheorie; Steuerungstheorie; Strukturwandel; Organisationskultur; Vereinsidentität; Entscheidungsprämissen

Improved bounds for the unsplittable flow problem - Kolman, Petr; Scheideler, Christian (SODA)

Compact, adaptive placement schemes for non-uniform requirements - Brinkmann, André; Salzwedel, Kay; Scheideler, Christian (SPAA)

Algorithms for fault-tolerant routing in circuit switched networks - Bagchi, Amitabha; Chaudhary, Amitabh; Scheideler, Christian; Kolman, Petr (SPAA)

Models and Techniques for Communication in Dynamic Networks - Scheideler, Christian (STACS)

Coherent nonlinear pulse propagation on a free-exciton resonance in a semiconductor - Nielsen, N. C.; Linden, S.; Kuhl, J.; Förstner, Jens; Knorr, A.; Koch, S. W.; Giessen, H. (Physical Review B)
The coherent exciton-light coupling in pulse propagation experiments on the A-exciton resonance in bulk CdSe is investigated over a broad intensity range. At low light intensities, polariton propagation beats due to interference between excited states on both polariton branches are observed. In an intermediate intensity regime, the temporal polariton beating is suppressed in consequence of exciton-exciton interaction. At the highest light intensities, self-induced transmission and multiple pulse breakup are identified as a signature for carrier density Rabi flopping. Exciton-phonon scattering is shown to gradually eliminate coherent nonlinear propagation effects due to enhanced dephasing of the excitonic polarization. Calculations using the semiconductor Maxwell-Bloch equations are in qualitative agreement with the experimental data.
Keywords: tet_topic_polariton

Data Warehouse in der Marktforschung - Analyse von Benutzeraktivitäten in virtuellen Welten - Schryen, Guido; Schoenen, Markus (Data Warehousing 2002)
Bei der Online-Marktforschung lässt sich mit Hilfe virtueller 3D-Welten das Konsumentenverhalten beobachten. Da die Struktur der dabei anfallenden Daten multidimensional ist und die marktforschungsrelevanten Anfragen eine hohe OLAP-Affinität aufweisen, wurde hierzu im Rahmen des Forschungsprojekts Benevit ein Data Warehouse konzipiert und realisiert. Im Rahmen einer Standardisierung der Protokollierung von Konsumentenaktivitäten und deren prototypischen Realisierung erwies sich der Data Warehouse/OLAP-Ansatz zur Speicherung, Analyse und Präsentation der Marktforschungsdaten als adäquates Instrumentenbündel.

Elektronisches Papier - Display-Technologie mit weitem Anwendungsspektrum - Schryen, Guido; Karla, Jürgen (Wirtschaftsinformatik)
Mit dem elektronischen Papier wird in der Displayforschung ein neuer materialtechnologischer Ansatz verfolgt: Elektronisches Papier besteht aus einer dünnen, flexiblen Folie, in der farbige Pigmente mittels elektrischer Felder ausgerichtet werden. Die Vorteile gegenüber traditionellen Technologien wie beispielsweise LCD-Displays bestehen zum einen in niedrigeren Herstellungskosten (niedrigere Produktionskosten und geringere Materialkosten) und einem geringeren Gewicht. Zum anderen entsteht eine bessere Lesbarkeit, da sich Reflexion, Kontrast und mögliche Betrachtungswinkel verbessern bzw. vergrößern. Diese Potenziale können bei Anzeigetafeln, Computerdisplays und mobilen Endgeräten ausgeschöpft werden. Mit der Eigenschaft, fast beliebige Materialien als Trägermedium zu verwenden, öffnet sich auch die Anwendungsmöglichkeit des biegsamen, elektronischen Mediums für Zeitungen und Zeitschriften. Die US-Unternehmen E Ink und Gyricon Media bieten eine zunehmend größere Produktpalette mit elektronischem Papier an.
Keywords: Elektronisches Papier; Elektronische Tinte; E Ink; Gyricon Media; Displays; Mobile Endger{\

Elektronische Zeitung - das Erbe Gutenbergs? - Schryen, Guido (i-com. Zeitschrift für interaktive und kooperative Medien)

Large Vocabulary Continuous Speech Recognition of Broadcast News - The Philips/RWTH Approach - Beyerlein, P.; Aubert, X.; Haeb-Umbach, Reinhold; Harris, M.; Klakow, D.; Wendemuth, A.; Molau, S.; Ney, N.; Pitz, Michael; Sixtus, A. (Speech Communication)
Automatic speech recognition of real-live broadcast news (BN) data (Hub-4) has become a challenging research topic in recent years. This paper summarizes our key efforts to build a large vocabulary continuous speech recognition system for the heterogenous BN task without inducing undesired complexity and computational resources. These key efforts included: - automatic segmentation of the audio signal into speech utterances; - efficient one-pass trigram decoding using look-ahead techniques; - optimal log-linear interpolation of a variety of acoustic and language models using discriminative model combination (DMC); - handling short-range and weak longer-range correlations in natural speech and language by the use of phrases and of distance-language models; - improving the acoustic modeling by a robust feature extraction, channel normalization, adaptation techniques as well as automatic script selection and verification. The starting point of the system development was the Philips 64k-NAB word-internal triphone trigram system. On the speaker-independent but microphone-dependent NAB-task (transcription of read newspaper texts) we obtained a word error rate of about 10%. Now, at the conclusion of the system development, we have arrived at Philips at an DMC-interpolated phrase-based crossword-pentaphone 4-gram system. This system transcribes BN data with an overall word error rate of about 17%.

A Joint Time Multiplex Receiver for UMTS and Galileo - Bischoff, Renke; Haeb-Umbach, Reinhold; Heinrichs, Guenther (ION-GPS 2002)
Currently the future satellite navigation system Galileo and the third generation mobile communications system UMTS are on their way to the market in Europe. cdma2000 is under development in the USA and, furthermore, a new civil GPS signal in L2 band and the new frequency band L5 are added. In a hybrid receiver for satellite navigation and mobile radio communications, the possibility of an additional usage of the mobile radio signals for navigation purposes could also be a remedy to one problem of satellite navigation systems, which is the reduced location accuracy inside of buildings and urban canyons. A hybrid receiver with two fully separated receiver branches would lead to an increased bill of material and to increased power consumption in the receiver. This paper, therefore, introduces a hybrid receiver capable of evaluating Galileo/GPS as well as UMTS/cdma2000 signals with reduced computational efforts. Furthermore, the proposed structure performs a constructive superposition of the incoming paths to improve location accuracy.

Employment of a multipath receiver structure in a combined GALILEO/UMTS receiver - Bischoff, Renke; Haeb-Umbach, Reinhold; Schulz, Wolfgang; Heinrichs, Guenther (IEEE 55th Vehicular Technology Conference (VTC 2002 Spring))
Current navigation systems like GPS (Global Positioning System) and its Russian counterpart GLONASS (Global Navigation Satellite System) only evaluate the direct signal path. The receivers treat the reflected paths also reaching the receiver antenna as disturbance which has to be suppressed. Multipath affects the tracking accuracy by resulting in a degeneration of the S-curve of the DLL (delay locked loop). Nowadays the future European systems GALILEO and GPSIIF/III with two new signals are on the way to the market and it is time to think about new receiver structures. Therefore we investigated if it is possible to use multipath for navigation constructively.
Keywords: combined GALILEO/UMTS receiver; delay locked loop; delay lock loops; DLL; Global Positioning System; GLONASS; GPS; GPSIIF/III; mobile satellite communication; multipath channels; multipath receiver structure; radio receivers; RAKE receiver; S-curve

Estimation of Bias Location Error due to Absence of the LOS-Signal in a UMTS-System - Hesse, Thomas; Bischoff, Renke; Schulz, Wolfgang; Haeb-Umbach, Reinhold (International Symposium on Location Based Services for Cellular Users (LOCELLUS 2002))
Current location methods for cellular communication systems TOA and E-OTD exploit time delays and time differences of various base station signals measured in a mobile phone to determine its location. These methods assume line-of-sight (LOS) connections to all utilized base stations. Since mobile radio channels are mainly characterized by scattered propagation paths and non-line-of-sight (NLOS) propagation, bias errors occur when measured time delays and time differences are utilized in position calculation algorithms. In this paper, the distribution of the time error due to NLOS propagation is estimated based on the channel model proposed in [1]. In combination with actual channel measurements in [2] the NLOS time error and its probability distribution function is estimated. With this information being determined for each received signal, position calculation algorithms can utilize the reliability information to enhance positioning accuracy. [1] L. J. Greenstein, V. Erceg, Y. S. Yeh, M. V. Clark, grqqA new path-gain/delay-spread propagation model for digital cellular channels'', IEEE Transactions on Vehicular Technology, Vol. 46, No. 2, May 1997 [2] H. Asplund, grqqWideband Channel Measurements in Central Stockholm'', T1P1.5/98-242r1

Leading, but not trailing, primes influence temporal order perception: Further evidence for an attentional account of perceptual latency priming. - Scharlau, Ingrid (Perception & Psychophysics)
Presenting a masked prime leading a target influences the perceived onset of the masking target. This priming effect is explained by the asynchronous updating model: The prime initiates attentional allocation toward its location, which renders a trailing target at the same place consciously available earlier. In 3 experiments, this perceptual latency priming by leading primes was examined jointly with the effects of trailing primes in order to compare the explanation of the asynchronous updating model with the onset-averaging and the P-center hypotheses. Exp 1 (n=15, mean age 27.1 yrs) showed that an attended, as well as an unattended, prime leads to perceptual latency priming. In addition, a large effect of trailing primes on the onset of a target was found. As Exp 2 (n=13, mean age 26.5 yrs) demonstrated, this effect is quite robust, although smaller than that of a leading prime. In Exp 3 (n=13, mean age 24.8 yrs), masked primes were used. Under these conditions, no influence of tra
Keywords: attention; leading primes; trailing primes; temporal order perception; perceptual latency priming; Adult; Attention; Female; Fixation; Ocular; Humans; Male; Perceptual Masking; Random Allocation; Time Perception; Visual Perception; Attention; Masking; Priming; Stimulus Frequency; Temporal Frequency; Temporal Order (Judgment)

Software Engineering and the Production of Surplus Value - Fuchs, Christian (Cultural Logic)

Particles get all dressed up - Meier, Torsten; Koch, S.W. (Physics World)
Physicists have realized during the last two decades that the physical properties of many condensed-matter systems are often best described in terms of lumps of charge, known as quasiparticles, rather than by electrons and ions. In a crystal under equlibrium conditions, for example, the mutual repulsion of the electrons leads to a cloud of positive charge surrounding each individual electron. This "dressing" of electrons leads to charge screening. In other words, a test charge placed far from an electron will feel the influence of a new entity with a smaller charge, rather than the charge on the "bare" electron.

Theory of the optical properties of semiconductor nanostructures - Meier, Torsten; Koch, S.W.; Hoyer, W.; Kira, M. (Physica E: Low-Dimensional Systems and Nanostructures)
A microscopic many-body theory describing the optical and electronic properties of semiconductors and semiconductor nanostructures is briefly reviewed. At the semiclassical level, the optical response is computed using Maxwell's equations together with the semiconductor Bloch equations which describe the dynamics of the diagonal and the off-diagonal terms of the reduced single-particle density matrix. These equations include the coupling between the semiconductor and the optical field as well as Coulomb many-body interactions among the optically excited carriers. Under quasi-equilibrium conditions, luminescence spectra can be obtained from absorption spectra on the basis of the Kubo–Martin–Schwinger relation for conditions usually limited to the regime of optical gain (lasers). More generally, light emission has to be computed at a fully quantum mechanical level leading to semiconductor luminescence equations.

Many-Body Correlation Effects in Photoexcited Semiconductor Heterostructures - Meier, Torsten; Reichelt, Matthias; Schlichenmaier, C.; Siggelkow, S.; Thomas, P.; Koch, S.W.; Weiser, S.; Sieh, C. (Germany NIC Series Vol. 9)

Optodynamik - Meier, Torsten; Koch, S.W. (Physik Journal)

Construction of Pseudorandom Functions - Fricke, Birgitta
Keywords: Diplomarbeit

Implementierung und Evaluation eines MDS-Blockcodes mit unabhängigen Paritätssymbolen - Hoppe, Ulrich

'Ich' war einmal. Zu literaturwiss. Problemhorizonten bei Subjektivität in Texten - Elit, Stefan (Das 'Ich' in der Frühen Neuzeit. Autobiographien – Selbstzeugnisse – Ego-Dokumente in geschichts- und literaturwissenschaftlicher Perspektive (Zeitenblicke 1 [2002], H. 2 [20.12.2002]))

Simple Routing Strategies for Adversarial Systems - Awerbuch, Baruch; Berenbrink, Petra; Brinkmann, André; Scheideler, Christian (FOCS)

SIMLAB-A Simulation Environment for Storage Area Networks - Berenbrink, Petra; Brinkmann, André; Scheideler, Christian (PDP)

Simple on-line algorithms for the maximum disjoint paths problem - Kolman, Petr; Scheideler, Christian (SPAA)

Implementation of a Rake Receiver Architecture into a Galileo Receiver - Bischoff, R.; Haeb-Umbach, Reinhold; Schulz, W.; Heinrichs, G. (1st ESA Workshop on Satellite Navigation User Equipment Technology (Navitec 2001))

Automatic generation of phonetic regression class trees for MLLR adaptation - Haeb-Umbach, Reinhold (IEEE Transactions on Speech and Audio Processing)
In this paper, it is shown that a correlation criterion is the appropriate criterion for bottom-up clustering to obtain broad phonetic class regression trees for maximum likelihood linear regression (MLLR)-based speaker adaptation. The correlation structure among speech units is estimated on the speaker-independent training data. In adaptation experiments the tree outperformed a regression tree obtained from clustering according to closeness in acoustic space and achieved results comparable with those of a manually designed broad phonetic class tree
Keywords: acoustic space; adaptation experiments; automatic generation; bottom-up clustering; broad phonetic class regression trees; correlation criterion; correlation methods; maximum likelihood estimation; maximum likelihood linear regression based speaker adaptation; MLLR adaptation; pattern clustering; phonetic regression class trees; speaker-independent training data; speech recognition; speech units; statistical analysis; trees (mathematics)

Multiclass linear dimension reduction by weighted pairwise Fisher criteria - Loog, M.; Duin, R.P.W.; Haeb-Umbach, Reinhold (IEEE Transactions on Pattern Analysis and Machine Intelligence)
We derive a class of computationally inexpensive linear dimension reduction criteria by introducing a weighted variant of the well-known K-class Fisher criterion associated with linear discriminant analysis (LDA). It can be seen that LDA weights contributions of individual class pairs according to the Euclidean distance of the respective class means. We generalize upon LDA by introducing a different weighting function
Keywords: approximate pairwise accuracy; Bayes error; Bayes methods; error statistics; Euclidean distance; Fisher criterion; linear dimension reduction; linear discriminant analysis; pattern classification; statistical analysis; statistical pattern classification; weighting function

Ladwig, Bernd, Militärische Interventionen zwischen Moralismus und Legalismus (Deutsche Zeitschrift für Philosophie, Berlin, 48, 2000) - Ficara, Elena (Servizio web italiano per la filosofia)

Schmücker, Reinold, Gibt es einen gerechten Krieg? (Deutsche Zeitschrift für Philosophie, Berlin, 48 2000) - Ficara, Elena (Servizio web italiano per la filosofia)

Wohlrapp, Harald, Krieg für Menschenrechte? (Deutsche Zeitschrift für Philosophie, Berlin, 48) - Ficara, Elena (Servizio web italiano per la filosofia)

Carter, Ian, L’idea di eguaglianza, Milano 2000 - Ficara, Elena (Bollettino telematico della filosofia politica)

High Dynamic Control of a Three-Level Voltage Source Converter Drive with Synchronous Motor and Active Front End - Böcker, Joachim; Janning, Jörg; Jebenstreit, Helmut (EPE’01, Graz)

Diagrammatic self-energy approximations and the total particle number - Schindlmayr, Arno; García-González, Pablo; Godby, Rex William (Physical Review B)
There is increasing interest in many-body perturbation theory as a practical tool for the calculation of ground-state properties. As a consequence, unambiguous sum rules such as the conservation of particle number under the influence of the Coulomb interaction have acquired an importance that did not exist for calculations of excited-state properties. In this paper we obtain a rigorous, simple relation whose fulfilment guarantees particle-number conservation in a given diagrammatic self-energy approximation. Hedin’s G0W0 approximation does not satisfy this relation and hence violates the particle-number sum rule. Very precise calculations for the homogeneous electron gas and a model inhomogeneous electron system allow the extent of the nonconservation to be estimated.

Exchange-correlation kernels for excited states in solids - Tatarczyk, Krzysztof; Schindlmayr, Arno; Scheffler, Matthias (Physical Review B)
The performance of several common approximations for the exchange-correlation kernel within time-dependent density-functional theory is tested for elementary excitations in the homogeneous electron gas. Although the adiabatic local-density approximation gives a reasonably good account of the plasmon dispersion, systematic errors are pointed out and traced to the neglect of the wave-vector dependence. Kernels optimized for atoms are found to perform poorly in extended systems due to an incorrect behavior in the long-wavelength limit, leading to quantitative deviations that significantly exceed the experimental error bars for the plasmon dispersion in the alkali metals.

Partner orientation and speaker’s knowledge as conflicting parameters in language production - Buhl, Heike M. (Journal of Psycholinguistic Research)
Two parameters of language production, the partner model and the mentally represented knowledge about a spatial constellation, are investigated with respect to their influence on spatial reference. At issue is whether the verbally expressed point of view in route directions is primarily influenced by the needs of the partner or by the underlying mental representation of the speaker stemming from his or her own experience with an object. Two experiments in which participants (N 5 90) were asked to produce a set of route directions are reported. The experimental situation was such that the point of view of the speaker did not correspond to the point of view of the partner. The results show that more participants localize from their own point of view than from the point of view of the partner. Discussion centers on the fact that speakers do not always behave in a truly partner-oriented manner.
Keywords: language production; partner model; mental representation; spatial point of view; route direction

Dynamics of Coulomb-correlated electron-hole pairs in disordered semiconductor nanowires - Meier, Torsten; Varga, I.; Schlichenmaier, C.; Maschke, K.; Thomas, P.; Koch, S.W. (Proceedings of the XXXVIth Rencontres de Moriond on Electronic Correlations: From Meso-Physics to Nano-Physics)
The dynamics of optically generated electron-hole pairs is investigated in a disordered semiconductor nanowire. The particle pairs are generated by short laser pulses and their dynamics is followed using the Heisenberg equation of motion. Is is shown that Coulomb-correlation acts against localization in the case of the two-interacting particles (TIP) problem. Furthermore, currents are generated using a coherent combination of full-gap and half-gap pulses. The subsequent application of a full-gap pulse after time τ produces an intraband echo phenomenon 2τ time later. The echo current is shown to depend on the mass ratio between the electrons and the holes.

body natural / body video / body politic - Adelmann, Ralf (https://nachdemfilm.de/issues/no-3-video-und-ueberwachung)

Sicherheit und Anwendungen des Advanced Encryption Standard (AES) Rijndael - Krummel, Volker
Keywords: Diplomarbeit

Brauer Addition-Subtraction Chains - Otto, Martin
Keywords: Diplomarbeit

Distributed Path Selection for Storage Networks - Berenbrink, Petra; Brinkmann, André; Scheideler, Christian (PDPTA)

Coloring non-uniform hypergraphs: a new algorithmic approach to the general Lovász local lemma - Czumaj, Artur; Scheideler, Christian (SODA)

Efficient, distributed data placement strategies for storage area networks (extended abstract) - Brinkmann, André; Salzwedel, Kay; Scheideler, Christian (SPAA)

A new algorithm approach to the general Lovász local lemma with applications to scheduling and satisfiability problems (extended abstract) - Czumaj, Artur; Scheideler, Christian (STOC)

A New Algorithmic Approach to the General Lovász Local Lemma with Applications to Scheduling and Satisfiability Problems - Czumaj, Artur; Scheideler, Christian (32nd ACM Symposium on Theory of Computing)

Multi-class Linear Feature Extraction by Nonlinear PCA - Duin, Robert P.W.; Loog, Marco; Haeb-Umbach, Reinhold (International Conference on Pattern Recognition (ICPR 2000))
The traditional way to find a linear solution to the feature extraction problem is based on the maximization of the class-between scatter over the class-within scatter (Fisher mapping). For the multi-class problem this is, however, sub-optimal due to class conjunctions, even for the simple situation of normal distributed classes with identical covariance matrices. We propose a novel, equally fast method, based on nonlinear PCA. Although still sub-optimal, it may avoid the class conjunction. The proposed method is experimentally compared with Fisher mapping and with a neural network based approach to nonlinear PCA. It appears to outperform both methods, the first one even in a dramatic way.

Data-driven Phonetic Regression Class Tree Estimation for MLLR Adaptation - Haeb-Umbach, Reinhold (International Conference on Spoken Language Processing (ICSLP 2000))

LDA derived cepstral trajectory filters in adverse environmental conditions - Lieb, M.; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech, and Signal Processing (ICASSP 2000))
Amongst several data driven approaches for designing filters for the time sequence of spectral parameters, the linear discriminant analysis (LDA) based method has been proposed for automatic speech recognition. Here we apply LDA-based filter design to cepstral features, which better match the inherent assumption of this method that feature vector components are uncorrelated. Extensive recognition experiments have been conducted both on the standard TIMIT phone recognition task and on a proprietary 130-words command word task under various adverse environmental conditions, including reverberant data with real-life room impulse responses and data processed by acoustic echo cancellation algorithms. Significant error rate reductions have been achieved when applying the novel long-range feature filters compared to standard approaches employing cepstral mean normalization and delta and delta-delta features, in particular when facing acoustic echo cancellation scenarios and room reverberation. For example, the phone accuracy on reverberated TIMIT data could be increased from 50.7% to 56.0%
Keywords: acoustic echo cancellation algorithms; adverse environmental conditions; automatic speech recognition; cepstral analysis; cepstral features; cepstral mean normalization; command word task; delta-delta features; delta features; echo suppression; error rate reductions; feature vector components; FIR filters; LDA derived cepstral trajectory filters; linear discriminant analysis; long-range feature filters; phone accuracy; real-life room impulse responses; reverberant data; spectral parameters; speech recognition; standard TIMIT phone recognition task

Multi-class Linear Dimension Reduction by Generalized Fisher Criteria - Loog, M.; Haeb-Umbach, Reinhold (International Conference on Spoken Language Processing (ICSLP 2000))

Decay properties of the one-particle Green function in real space and imaginary time - Schindlmayr, Arno (Physical Review B)
The decay properties of the one-particle Green function in real space and imaginary time are systematically studied for solids. I present an analytic solution for the homogeneous electron gas at finite and at zero temperature as well as asymptotic formulas for real metals and insulators that allow an analytic treatment in electronic-structure calculations based on a space-time representation. The generic dependence of the decay constants on known system parameters is used to compare the scaling of reciprocal-space algorithms for the GW approximation and the space-time method.

Biographische Übergänge und Alter als Determinanten der Eltern-Kind-Beziehung im Erwachsenenalter - Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)
Gegenstand des Artikels ist die Beziehung Erwachsener zu ihren Eltern, die vor dem Hintergrund individuationstheoretischer Konzeptionen hinsichtlich Abgrenzung und Verbundenheit sowie weiterer relevanter Beziehungsmerkmale untersucht wird. Annahme ist, daß sich die Beziehung im Erwachsenenalter mit dem Absolvieren biographischer Übergänge (Auszug aus dem Elternhaus, Partnerschaft, Erstelternschaft) hin zu mehr Abgrenzung verändert, während die Verbundenheit in der Beziehung unverändert hoch sein sollte. Zur Untersuchung dieser Hypothesen bearbeiteten 114 junge Erwachsene und 27 Erwachsene im mittleren Alter neun zentrale Skalen des Network of Relationships Inventory. Die Ergebnisse zeigen Einflüsse der Lebenssituation wie auch des Alters auf Abgrenzung, aber auch Verbundenheit. Dabei ist zwischen der Beziehung zu Mutter und Vater zu unterscheiden. Im mittleren Erwachsenenalter führt eine Verbesserung der Beziehung zum Vater zur Angleichung der Beziehung zum Vater an die zur Mutter.

Semiclassical Effective Hamiltonian For Coupled Electronic And Nuclear Optical Response - Meier, Torsten; Chernyak, V.; Tretiak, S.; Tsiper, EV..; Mukamel, S. (Condensed Matter Theories)

Verfahren des Authentischen. Überwachungskameras im Kontext des Fernsehens - Adelmann, Ralf (https://nachdemfilm.de/issues/no-2-show-reality-reality-shows)

Geschichtsschreibung oder Roman? Zur Konstitutionslogik von Geschichtserzählungen zwischen Schiller und Ranke (1780–1824) - Süßmann, Johannes
Keywords: Schiller; Kleist; Ranke; Leopold von; Gatterer; Johann Christoph; Darstellungsfragen; Universalhistorie; Humboldt; Wilhelm von; Wieland; Christoph Martin

Aufdringliche Geschichten. Zum Verhältnis von Musik und Werbung - Jacke, Christoph; Jünger, Sebastian; Zurstiege, Guido (Populäre Musik im kulturwissenschaftlichen Diskurs)

Locally Efficient On-Line Strategies for Routing Packets Along Fixed Paths - Berenbrink, Petra; Scheideler, Christian (SODA)

Simple Competitive Request Scheduling Strategies - Berenbrink, Petra; Riedel, Marco; Scheideler, Christian (SPAA)

Design of the PRESTO Multimedia Storage Network (Extended Abstract) - Berenbrink, Petra; Riedel, Marco; Scheideler, Christian (International Workshop on Communication and Data Management in Large Networks (CDMLarge))

From Static to Dynamic Routing: Efficient Transformations of Store-and-Forward Protocols - Scheideler, Christian; Vöcking, Berthold (STOC)

The Philips/RWTH system for transcription of broadcast news - Beyerlein, Peter; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Harris, Matthew J.; Klakow, Dietrich; Wendemuth, Andreas; Molau, Sirko; Pitz, Michael; Sixtus, Achim (Eurospeech)
This paper contains a description of the Philips/RWTH 1998 HUB4 system which has been build in a joint e ort of Philips Research Laboratories Aachen and Aachen University of Technology. We will focus our discussion on recent improvements compared to the original 1997 HUB4 system and evaluate them on the HUB4'97 evaluation data. The paper will deal with 1. a rough system overview including feature extraction, acoustic training, audio stream segmentation, and decoding 2. log-linear interpolation of distance-language models, 3. and the integration of various acoustic and language models via Discriminative Model Combination (DMC). The performance of the described system is 23% (relative) better than the performance of the 1997 Philips HUB4 system. A word error rate of 17.9% was achieved on the 1997 HUB4 evaluation set, compared to 23.5% using the original 1997 system.

The Philips/RWTH System for Transcription of Broadcast News - Beyerlein, Peter; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Harris, Matthew J.; Klakow, Dietrich; Wendemuth, Andreas; Molau, Sirko; Pitz, Michael; Sixtus, Achim (Broadcast News Transcription and Understanding Workshop, Washington)
This paper contains a description of the Philips/RWTH 1998 HUB4 system which has been build in a joint e ort of Philips Research Laboratories Aachen and Aachen University of Technology. We will focus our discussion on recent improvements compared to the original 1997 HUB4 system and evaluate them on the HUB4'97 evaluation data. The paper will deal with 1. a rough system overview including feature extraction, acoustic training, audio stream segmentation, and decoding 2. log-linear interpolation of distance-language models, 3. and the integration of various acoustic and language models via Discriminative Model Combination (DMC). The performance of the described system is 23% (relative) better than the performance of the 1997 Philips HUB4 system. A word error rate of 17.9% was achieved on the 1997 HUB4 evaluation set, compared to 23.5% using the original 1997 system.

Investigations on inter-speaker variability in the feature space - Haeb-Umbach, Reinhold (ICASSP99 Phoenix, AZ)
We apply Fisher variate analysis to measure the effectiveness of speaker normalization techniques. A trace criterion, which measures the ratio of the variations due to different phonemes compared to variations due to different speakers, serves as a first assessment of a feature set without the need for recognition experiments. By using this measure and by recognition experiments we demonstrate that cepstral mean normalization also has a speaker normalization effect, in addition to the well-known channel normalization effect. Similarly vocal tract normalization (VTN) is shown to remove inter-speaker variability. For VTN we show that normalization on a per sentence basis performs better than normalization on a per speaker basis. Recognition results are given on Wall Street Journal and Hub-4 databases

An Investigation of Cepstral Parameterisations for Large Vocabulary Speech Recognition - Haeb-Umbach, Reinhold; Loog, Marco (Eurospeech)
We examined variants of MFCC and PLP cepstral parameterisations in the context of large vocabulary continuous speech recognition under different acous-tical environmental conditions: Compared to MFCC, mel-frequency PLP uses a cubic root intensity-to-loudness law, and an LPC analysis is applied to the mel-warped spectrum. In LPC-smoothed MFCC, the only difference to MFCC is the additional LPC smoothing of the warped spectrum. While neither technique was able to significantly outperform the MFCC parameterisation in our setup which includes an LDA feature transformation, feature set combination via DMC at the acoustic likelihood level and via ROVER at the recognized word level delivered small but consistent improvements.

A study of broadcast news audio stream segmentation and segment clustering - Harris, Matthew J.; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Beyerlein, Peter (Eurospeech)
In transcription of broadcast news, dividing the signal into homogeneous segments, and clustering together similar segments is important. Decoding a complete broadcast news program in one chunk is technically di cult. Also, through creation of homogeneous clusters of segments, improvement from adaptation can be increased. Two systems of segmentation and clustering are compared. The best system used the BIC algorithm to produce long, homogeneous segments, and a nearest neighbour bottom-up agglomerative clustering algorithm to produce homogeneous clusters. Adaptation brought a word error rate (WER) improvement from 23:4% to 21:0% using the automatic segmentation and clustering, compared to an improvement from 21:8% to 20:0% using a handmade \correct" segmentation and clustering.

Leviathan oder Trickster? Erzählstrategien in aktueller Erkenntniskritik und Wissenschaftsforschung - Weber, Jutta (IWT-Paper 24. Tagungsdokumentation „Theorien über Theorien über Theorien“. 1. - 2. Juli 1999. Institut für Wissenschafts- und Technikforschung, Universität Bielefeld, S. 91-96)

Contested Meanings: Nature in the Age of Technoscience - Weber, Jutta (Die Zukunft des Wissens. XVIII. Deutscher Kongreß für Philosophie. Konstanz 1999)

Efficient Communication Strategies for Ad-Hoc Wireless Networks (Extended Abstract) - Adler, Micah; Scheideler, Christian (SPAA)

Improved Bounds for Acyclic Job Shop Scheduling (Extended Abstract) - Feige, Uriel; Scheideler, Christian (STOC)

Automatic Transcription of English Broadcast News - Beyerlein, Peter; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Klakow, Dietrich; Ullrich, Meinhard; Wendemuth, Andreas; Wilcox, Patricia (DARPA Broadcast News Transcription and Understanding Workshop, Landsdowne)
In this paper the Philips Broadcast News transcription system is described. The Broadcast News task aims at the recognition of "found" speech in radio and television broadcasts without any additional side information (e.g. speaking style, background conditions). The system was derived from the Philips continuous mixture density crossword HMM system, using MFCC features and Laplacian densities. A segmentation was performed to obtain sentence-like partitions of the broadcasts. Using data-driven clustering, the obtained segments were grouped into clusters with similar acoustic conditions for adaptation purposes. Gender independent word-internal and crossword triphone models were trained on 70 hours of the HUB4 training data. No focus condition specific training was applied. Channel and speaker normalization was done by mean and variance normalization as well as VTN and MLLR. The transcription was produced by an adaptive multiple pass decoder starting with phrase-bigram decoding using word-internal triphones and finishing with a phrase-trigram decoding using MLLR-adapted crossword models.

Acoustic Modeling in the Philips Hub-4 Continuous-Speech Recognition System - Haeb-Umbach, Reinhold; Aubert, Xavier L.; Beyerlein, Peter; Klakow, Dietrich; Ullrich, Meinhard; Wendemuth, Andreas; Wilcox, Patricia (DARPA Broadcast News Transcription and Understanding Workshop, Landsdowne)
In this paper we describe some characteristics of the acoustic modeling used in the Philips continuous-speech recognition system for the DARPA Hub-4 1997 evaluation, which are related to robustness issues. We aimed at a conceptually simple system: We trained two model sets on 70 hours of the Hub-4 training data, one for within-word and one for cross-word decoding. These model sets were used for both genders and all environmental conditions. In order to be able to do so, channel normalization (mean, variance normalization) and speaker normalization (vocal tract length normalization, realized by an appropriate shift of the center frequencies of the mel filter bank) have been applied, as well as adaptation techniques. MLLR-based unsupervised batch adaptation on clusters of segments was conducted both after a first within-word decoding and a cross-word decoding pass. The training strategy and the effects of the various normalization and adaptation techniques will be discussed in the paper.

Language-Model Investigations related to Broadcast News - Klakow, Dietrich; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Beyerlein, Peter; Ullrich, Meinhard; Wendemuth, Andreas; Wilcox, Patricia (DARPA Broadcast News Transcription and Understanding Workshop, Landsdowne)
In this paper we present some experiments that have been performed while developing language models for the PHILIPS Broadcast News system. Three main issues will be discussed: construction of phrases, adaptation of remote corpora to this task, and the combination of the different models. Also, perplexities on the 1997 evaluation data are reported.

A Study on Speaker Normalization Using Vocal Tract Normalization and Speaker Adaptive Training - Welling, L.; Haeb-Umbach, Reinhold; Aubert, X.; Haberland, N. (ICASSP 1998, Seattle)
Although speaker normalization is attempted in very different manners, vocal tract normalization (VTN) and speaker adaptive training (SAT) share many common properties. We show that both lead to more compact representations of the phonetically relevant variations of the training data and that both achieve improved error rate performance only if a complementary normalization or adaptation operation is conducted on the test data. Algorithms for fast test speaker enrollment are presented for both normalization methods: in the framework of SAT, a pre-transformation step is proposed, which alone, i.e. without subsequent unsupervised MLLR adaption, reduces the error rate by almost 10% on the WSJ 5k test sets. For VTN, the use of a Gaussian mixture model makes obsolete a first recognition pass to obtain a preliminary transcription of the test utterance at hardly and loss in performance.

Spectra and total energies from self-consistent many-body perturbation theory - Schindlmayr, Arno; Pollehn, Thomas Joachim; Godby, Rex William (Physical Review B)
With the aim of identifying universal trends, we compare fully self-consistent electronic spectra and total energies obtained from the GW approximation with those from an extended GWΓ scheme that includes a nontrivial vertex function and the fundamentally distinct Bethe-Goldstone approach based on the T matrix. The self-consistent Green’s function G, as derived from Dyson’s equation, is used not only in the self-energy but also to construct the screened interaction W for a model system. For all approximations we observe a similar deterioration of the spectrum, which is not removed by vertex corrections. In particular, satellite peaks are systematically broadened and move closer to the chemical potential. The corresponding total energies are universally raised, independent of the system parameters. Our results, therefore, suggest that any improvement in total energy due to self-consistency, such as for the electron gas in the GW approximation, may be fortuitous.

Systematic vertex corrections through iterative solution of Hedin's equations beyond the GW approximation - Schindlmayr, Arno; Godby, Rex William (Physical Review Letters)
We present a general procedure for obtaining progressively more accurate functional expressions for the electron self-energy by iterative solution of Hedin's coupled equations. The iterative process starting from Hartree theory, which gives rise to the GW approximation, is continued further, and an explicit formula for the vertex function from the second full cycle is given. Calculated excitation energies for a Hubbard Hamiltonian demonstrate the convergence of the iterative process and provide further strong justification for the GW approximation.